The effect of leverage manipulation on real estate firms’ financial risk: Based on the interest conflicts perspective - Liwen Huang; Liangxing Yu; Wei Huang (PLoS ONE, 2025)
From the perspective of interest conflicts, this study investigates the relationship between corporate leverage manipulation and financial risk using a sample of A-share listed real estate firms in China from 2009 to 2023. Employing a two-way fixed effects model, the main findings are as follows: (1) Leverage manipulation significantly increases the level of financial risk among real estate firms; (2) Mechanism analysis reveals a collusion effect between controlling shareholders and management, as well as between external auditors and management, both of which significantly amplify the impact of leverage manipulation on financial risk. These findings support the collusion effect hypothesis and reject the monitoring effect hypothesis; (3) Heterogeneity tests show that the impact of leverage manipulation on financial risk is more pronounced in non-state-owned enterprises, in firms dominated by transactional institutional investors, and in regions with lower reliance on land finance. This study uncovers the intrinsic link between leverage manipulation and financial risk in the real estate sector and provides important policy implications for regulators aiming to improve and standardize financial risk management in the industry.